De’troit / Muhammad Nizam Azhar and Nur Nazlin Zahri - Azhar, Muhammad Nizam; Zahri, Nur Nazlin (Universiti Teknologi MARA, Kedah, 2018)
Portable speaker is a product that is handy in size and easy to be carried which is suitable for personal usage. The design of the product was become the main topic on these days and one of the causes is the design is unsuit-able. The existing design is also too mainstream and need more material. The purpose of this study is to understand the principles, problems, and approaches of the user and the product. The objective of the research is to produce a modern and latest portable speaker influenced by trans hi-tech design especially for the youngster. The qualitative study which involved an interview was used to get primary data. The research is focused on the design in solving problems that based on the interview. The research found the opportunity of using new material in the product which has become the major factor in producing a portable sepaker influenced by the trans hi-tech design.